Perancangan Ulang Wire Rope Pada Sistem Hoisting Overhead Travelling Crane Kapasitas 55 Ton Di Area Crusher PT. Semen Baturaja (Persero) Tbk Indonesia - Riski Dwi Prasetio; Syafri Syafri; Mustafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hoisting system on overhead traveling crane capacity of 55 tons in the crusher area of PT. Semen Baturaja is designed for material handling processes, especially if it is needed in the event of equipment disruption or trouble in the area and also during factory shutdown. The main components of the hoisting mechanism consist of wire rope, pulley, drum, hook, lifting motor and mechanical brake. In this design initial data obtained from observations of objects and through discussions with resource persons in the field. Calculations and design up to determine the safe number of all the main components is obtained based on the appropriate literature. In this design the type of wire rope 6 x 41 + 1 Fiber 32 mm diameter is obtained and the estimated life of the wire rope is approximately 1 year with the assumption of 24 hour usage. Keyword : Overhead travelling crane, hoisting system, wire rope,design